2019
DOI: 10.24874/jsscm.2019.13.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Flow Control With Vortex Generators Around a Symmetrical Airfoil at High Attack Angles

Abstract: The flow on the upper surface of NACA 0015 airfoil is subject to an adverse pressure gradient when the incidence increases. This leads to the boundary layer separation which causes losses in the aerodynamic performances. Control using Vortex Generators (VGs) is a simple passive mean used to delay or eliminate the flow separation from the wall. The two main objectives of the experimental work performed consist in the optimization by experimental design method "DoE" of a new VGs configuration, inspired by Lin's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…This jet-age technology provides improved aileron response, reduced turning time, a 7% reduction in stall speed, and reduced landing and take-off roll [21,22]. Tebbiche and Boutoudj [23] designed and studied VGs in a wind tunnel and found that they decreased drag by about 13% at a 15 • stall angle, and that drag reduction would result in increased fuel economy and reduced exhaust gas and aircraft noise. Vignesh et al [24] reported that the VG in a Clark Y type airfoil would enhance the payload and take-off as well as reduce landing distances for short runways and produce desirable changes in the stall characteristics of an airfoil wing.…”
Section: Introductionmentioning
confidence: 99%
“…This jet-age technology provides improved aileron response, reduced turning time, a 7% reduction in stall speed, and reduced landing and take-off roll [21,22]. Tebbiche and Boutoudj [23] designed and studied VGs in a wind tunnel and found that they decreased drag by about 13% at a 15 • stall angle, and that drag reduction would result in increased fuel economy and reduced exhaust gas and aircraft noise. Vignesh et al [24] reported that the VG in a Clark Y type airfoil would enhance the payload and take-off as well as reduce landing distances for short runways and produce desirable changes in the stall characteristics of an airfoil wing.…”
Section: Introductionmentioning
confidence: 99%
“…Les résultats obtenus ont montré qu'il y a une réduction de la force de traînée jusqu'à 10%. [7] Dans ce travail, une simulation numérique a été faite, à l'aide du code de calcul -Fluent-, de l'écoulement d'air sur une pale d'éolienne 'FX-63-137' dans le but d'étudier le comportement dynamique autour du profil en absence et en présence des générateurs vortex (GV). Les effets de l'angle d'incidence du vent et aussi de la position des générateurs de vortex par rapport au profil ont été examinés.…”
Section: Introductionunclassified